Measurement of pocket beach morphology using geographic information technology: the MAPBeach toolbox - Horta, Joao; Moura, Delminda; Gabriel, Selma; Ferreira, oscar (Journal of coastal research, 2013)
The measurement and evaluation of the morphological response of a beach to changes on wave conditions has been the subject of several studies over the past years. This paper presents and discusses a methodology to compute variations in pocket beaches after morphological monitoring performed trough topographical surveys. The GIS toolbox, GIS tools for Morphological Analysis at Pocket Beaches, was developed to simplify the morphological analysis of pocket beaches. The obtained data were compiled and used to produce digital terrain models in a Geographic Information System (GIS) environment. The developed GIS toolbox enabled a quick and efficient evaluation of the morphological changes occurred at the selected beaches, associated to different forcing conditions, through the determination and further analysis of a set of pre-defined morphological parameters, including beach profiles, beach slope, elevation, volumes, beach curvature, beach rotation, among others. The developed tools proved to be robust and easy to operate, facilitating both the scientific analysis as the determination of useful parameters for coastal management, being therefore of broad application.